Multiple Mathematical Representations According to the (Lesh) Model of High School Students and Its Relationship to Their Mathematical Ability - ABED, RIHAB KHALEEL; HASSAN, DR. AREEJ KHUDER (The journal of contemporary issues in business and government, 2021)
The Research aim is to determine the essence of the relationship between students' mathematical representations in high school and their mathematical ability. The following null hypotheses were established in order to achieve the research objectives: There is no statistically significant difference at the level of (0.05) between the average true performance and the average hypothetical performance of third-grade intermediate students in the General Directorate of Education in Baghdad / Rusafa 1/, Al-Rashdiyah district, on the multiple mathematical representations test prepared for the aforementioned purpose and according to the gender There is no statistically significant difference at the level of (0.05) between the average true performance and the average hypothetical performance of third-grade intermediate students in the General Directorate of Education in Baghdad / Rusafa 1/, Al-Rashdiyah district, on the mathematical ability test prepared for the aforementioned purpose, according to the gender There is no correlation relationship at the level of significance (0.05) between Multiple mathematical representations and Mathematics ability among third-grade middle school students in the General Directorate of Education in Baghdad / Rusafa 1/ district AL- Rashidiya, according to the gender variable. After identifying the research community, which represented high school students in the General Directorate of Education in Baghdad /Rusafa 1/, Al-Rashidiya district, third-grade intermediate students were determined in order to conduct the field study.Thus, the size of the research sample reached (269) male and female students (134) male and (135) female students. For the purpose of collecting data for this research, two tests were constructed: Test of multiple mathematical representations according to the Lesch model (Lesh):in its finalized form of (25 ) A test paragraph with (21) of the objective type and (4) of the Assay Mathematical Ability Test: It consists of (28) test items of the objective Then, appropriate statistical analyzes were conducted for the two test items, and to verify the psychometric properties of them. After adopting the statistical tools for analyzing the results of applying the two tests, the results reached showed that: The third-grade intermediate students have the research sample of multiple mathematical The superiority of females over males in the multiple mathematical representations Third-grade students possessing the average of the research sample, the mathematical Females surpass males in the mathematically ability There is a positive and strong correlational relationship among students between multiple mathematical representations and ability They have a positive In light of the research results, several recommendations were made, including: Curriculum designers in the Ministry of Education must emphasize the multiple mathematical representations of students when building and developing mathematics curricula, as well as adding exercises and heritage activities that develop their mathematical Exposing students to various practical and life situations that require them to use mathematical representations and to employ their mathematical 3. Raising the awareness of mathematics teachers of the importance of multiple mathematical representations and the mathematical ability of students as one of the important goals of teaching mathematics advocated by the National Council of Mathematics Teachers( NCTM, 2000). According to the results, several proposals were suggested, including: Conduct a similar study for the elementary and preparatory stages, to see if they possess Multiple mathematical representations and types of Mathematical Conduct a similar analysis in other governorates for the same grade and compare the Conduct experimental studies to employ some software to employ various mathematical representations that will help students improve their mathematical